A hidden structural vulnerability in the thrombospondin-2 deficient aorta increases the propensity to intramural delamination. (July 2017) - Bellini, C.; Kristofik, N.J.; Bersi, M.R.; Kyriakides, T.R.; Humphrey, J.D.
Abstract: Mice lacking thrombospondin-2 (TSP2) represent an animal model of impaired collagen fibrillogenesis. Collagen constitutes ~1/3 of the wall of the normal murine descending thoracic aorta (DTA) and is thought to confer mechanical strength at high pressures. Microstructural analysis of the DTA from TSP2-null mice revealed irregular and disorganized collagen fibrils in the adventitia and at the interface between the media and adventitia. Yet, biaxial mechanical tests performed under physiologic loading conditions showed that most mechanical metrics, including stress and stiffness, were not different between mutant and control DTAs at 20- and 40-weeks of age, thus suggesting that the absence of TSP2 is well compensated under normal conditions. A detailed bilayered analysis of the wall mechanics predicted, however, that the adventitia of TSP2-null DTAs fails to engage at high pressures, which could render the media vulnerable to mechanical damage. Failure tests confirmed that the pressure at which the DTA ruptures is significantly lower in 20-week-old TSP2-null mice compared to age-matched controls (640±37 vs. 1120±45 mmHg). Moreover, half of the 20-week-old and all 40-week-old mutant DTAs failed by delamination, not rupture. This delamination occurred at the interface between the media and the adventitia, with separation planes often observed at ~45 degrees with respect to the circumferential/axial directions. Combined with the observed microstructural anomalies, our theoretical-experimental biomechanical results suggest that TSP2-null DTAs are more susceptible to material failure when exposed to high pressures and this vulnerability may result from a reduced resistance to shear loading at the medial/adventitial border. Graphical abstract: Highlights: Absence of TSP-2 impairs proper formation and organization of collagen in the aorta. The aorta behaves normally within the physiological range of pressures. The load is not properly transferred to the adventitia at pressures above systolic. The aorta fails with media/adventitia delamination. Shear stress-induced relative motions might be responsible for delamination.